1986
DOI: 10.1136/adc.61.1.24
|View full text |Cite
|
Sign up to set email alerts
|

C reactive protein in the evaluation of febrile illness.

Abstract: Children with acute otitis media were excluded because they are routinely treated with antibiotics. Children with tonsillitis were excluded because a separate study was being carried out of tonsillitis. There were 70 girls and 84 boys. Seventy eight (51%) children were less than 2 years old, 42 (27%) between 2 and 6 years, and 34 (22%) over 6 years old. The mean age was 3 years 4 months with a range of 2 months to 14 years.The outpatients received a questionnaire for follow up of the symptoms and signs of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
55
1
2

Year Published

1988
1988
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(62 citation statements)
references
References 18 publications
4
55
1
2
Order By: Relevance
“…Accordingly, they are expected to be higher in bacterial than in viral infections. In the present study, CRP, ESR and ANC were higher in patients with PNC pneumonia than in those with viral pneumonia; this is in accordance with previous studies comparing bacterial infections, usually diagnosed by cultural methods, with viral infections [4,5]. On the other hand, CRP was not elevated, being under 60 mg·L -1 , in over half of the cases with PNC aetiology.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Accordingly, they are expected to be higher in bacterial than in viral infections. In the present study, CRP, ESR and ANC were higher in patients with PNC pneumonia than in those with viral pneumonia; this is in accordance with previous studies comparing bacterial infections, usually diagnosed by cultural methods, with viral infections [4,5]. On the other hand, CRP was not elevated, being under 60 mg·L -1 , in over half of the cases with PNC aetiology.…”
Section: Discussionsupporting
confidence: 80%
“…Since the assessment of the specific microbial aetiology of pneumonia is difficult, nonspecific inflammatory parameters and the type of infiltration in a chest radiograph are widely used for this purpose. In children, serum C-reactive protein (CRP) appears to be more useful than the conventionally used parameters, white blood cell count (WBC) or erythrocyte sedimentation rate (ESR) [4,5]. The absolute neutrophil count (ANC) is usually elevated in bacteraemic infections [6].…”
mentioning
confidence: 99%
“…All preterm infants in this study with confirmed bacterial or fungal infection also presented CRP levels above 40 mg/L. PUTTO et al (1986) 26 , studying 154 children with fever, reported that values of CRP between 20 and 40 mg/L may be found in both viral and bacterial infections, and that levels over 40 mg/L detect 79% of the bacterial infections, with 90% specificity. SAIJO et al (1996) 27 observed that most of the children with infection caused by RSV present a low CRP level.…”
Section: Discussionmentioning
confidence: 99%
“…A normal CRP in a patient with symptoms of respiratory infection usually indicates a self-limiting infection that does not require referral to hospital or antibiotic treatment, although it may also be observed early in the presentation of an illness [29]. A systematic review and meta-analysis of 13 studies in primary care demonstrated CRP testing led to significantly reduced antibiotic prescribing at the index consultation [19].…”
Section: Discussionmentioning
confidence: 99%